Deep cervical lymph node ligation aggravates AD‐like pathology of APP/PS1 mice. (10th October 2018) - Wang, Linmei; Zhang, Yanli; Zhao, Ying; Marshall, Charles; Wu, Ting; Xiao, Ming
Abstract: The imbalance between production and clearance of amyloid‐beta (Aβ) is a key step in the onset and development of Alzheimer's disease (AD). Therefore, reducing Aβ accumulation in the brain is a promising therapeutic strategy for AD. The recently discovered glymphatic system and meningeal lymphatic vasculature have been shown to be critical for the elimination of interstitial waste products, especially Aβ, from the brain. In the present study, ligation of deep cervical lymph nodes was performed to block drainage of this system and explore the consequences on Aβ‐related pathophysiology. Five‐month‐old APP/PS1 mice and their wild‐type littermates received deep cervical lymphatic node ligation. One month later, behavioral testing and pathological analysis were conducted. Results demonstrated that ligation of dcLNs exacerbated AD‐like phenotypes of APP/PS1 mice, showing more severe brain Aβ accumulation, neuroinflammation, synaptic protein loss, impaired polarization of aquaporin‐4 and deficits in cognitive and exploratory behaviors. These results suggest that brain lymphatic clearance malfunction is one of the deteriorating factors in the progression of AD, and restoring its function is a potential therapeutic target against AD.